Kim e a literatura colonial de língua inglesa - Zacchi, J. Zacchi (2006)
Kim is not only one of Rudyard Kipling’s most important books, but it also occupies position of prominence in English language literature. It was released in 1901, when India, where the novel is set, was still a British possession and twelve years after Indian born Kipling had migrated to England. The relationships between the Eastern and the British characters in the novel suggest a stereotyped view of racial and cultural differences. These relationships will be analysed in the context of English colonial literature and within the framework of Edward Said’s (1995) Orientalism. Kim belongs to the second stage of the English colonial literature, which embodied the point of view of the British and sought to assert the rightness of empire. Orientalism is a Western style for describing and having authority over the Orient. It is particularly concerned with the representation of its inhabitants through the use of syntheses and stereotypes.